Understanding the Dynamics of Cashless Payment System: The Effects of Technology Advancement, Security Concerns, and Competition on Merchant Adoption in Hyderabad, India - Madhavedi, Sudhakar; Hoo, Wong Chee; Goh, Khang Wen; Liau, Chee How; Cheng, Aw Yoke; Pandey, Ram Kinker (Journal of Ecohumanism, 2024)
This study examined the impact of technology advancement, security concerns, and competition on the adoption of Cashless Payment Systems (CPS) by merchants in Hyderabad City, India using a descriptive research design. A semi-structured questionnaire was administered to business heads, and the data was analyzed using frequency tables, means, correlation, and multiple regression analysis. The study findings revealed that technology advancement, security concerns, and competition significantly influence the process of adoption of CPS. The study recommends that entrepreneurs nationwide recognize CPS, as an opportunity to show case their unique and distinctiveness to capture market share. In light of limited cash availability, digital transactions, classified by the RBI as 'prepaid payment instruments,' are becoming increasingly important, driving more merchants to embrace digital money for better transparency, scalability, accountability and sustainability.